2011
DOI: 10.1007/s00520-011-1348-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of palonosetron on electrocardiographic parameters in cancer patients: a prospective study

Abstract: Palonosetron seems to have no acute arrhythmogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy. The primary objective of this study was to demonstrate in paediatric patients the non-inferiority of palonosetron, versus ondansetron, during the acute phase of the first on-study chemotherapy cycle.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy. The primary objective of this study was to demonstrate in paediatric patients the non-inferiority of palonosetron, versus ondansetron, during the acute phase of the first on-study chemotherapy cycle.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to laboratory values, vital signs, and ECG findings, there were no pronounced differences between palonosetron and older 5-HT 3 RAs. The studies analyzed here did not thoroughly evaluate QTc measures; however, recent studies in patients with cancer 17,18 and a thorough QTc study in healthy subjects that used a positive control (ie, moxifloxacin) 16 demonstrated no significant QTc changes associated with palonosetron. This is in contrast to evidence of significant dose-related QTc prolongation with ondansetron, which led to the removal of the 32-mg single dose from its label, 30 and an increased risk of cardiac arrhythmias with IV dolasetron, which is no longer recommended.…”
Section: Discussionmentioning
confidence: 94%
“…As the first combination antiemetic developed, it targets two critical molecular pathways (substance P/NK 1 RA; serotonin/5-HT 3 RA) associated with CINVand offers guidelineconsistent prophylaxis with a single dose (and DEX). Palonosetron was selected for the combination over older generation 5-HT 3 RAs due to its distinctive pharmacological properties [20,21], safe cardiac profile [22][23][24][25], and proven clinical efficacy [26][27][28][29]. In mechanistic studies, netupitant and palonosetron have exhibited synergistic effects when inhibiting the substance P response [30].…”
Section: Evaluation Of Nepa In Patients Receiving Carboplatinmentioning
confidence: 99%